O processo de municipalização da socioeducação expresso em microrregiões do Sudoeste do Paraná - Pereira, Monica (2018)
The research has as its theme the municipalization of socioeducation in the small municipalities of the Southwest Microregion of Paraná. The purpose of this study is to analyze how the municipalization of this service has been constituted in accordance with the principles of the Statute of the Child and Adolescent (ECA) and with the parameters of the National Socio-Educational Service System (SINASE) and the Single Social Assistance System YOUR). It was proposed as a research problem to investigate whether the process of operationalization of socio-educational measures in open environments in small municipalities in the Southwest Microregion of Paraná allows these to be carried out in accordance with legislation protecting adolescents. The objective was to analyze the efficiency of the process of operationalization of socio-educational measures in open environments in the small municipalities of the Southwest Microregion of Paraná from 2012 to 2016. The discussion sought to apprehend socio-education in the context of capitalism; to investigate the process of municipalization of socio-educational measures and to identify the advances and challenges encountered in the daily life of the municipalities about the operationalization of socio-educational measures. To that end, a deepening and theoretical study, critical bibliographical review and reflection on the process of municipalization of these measures had been carried out. The approach towards the policy of care of children and adolescents in the Southwest Microregion of Paraná was made through the conduction of field and documentary research with the Municipal Secretaries of Social Assistance. The qualitative approach was used and field research was based on semi-structured interviews with the managers and technicians who work alongside the social assistance policy in the municipalities of the Southwest Microregion of Paraná. The research universe was composed of 27 municipalities, of which 07 were the final sample, with a total of 16 interviewees, and the sample was defined based on pre-established criteria. The interviews were then recorded and transcribed as authorized by the respondents. The speeches will not be presented by the subject interviewed, but added to each other throughout the course of the analysis, with only the differentiation per municipality. It was decided to identify the subjects as follows: Municipality 1 (M1); Municipality 2 (M2); Municipality 3 (M3); Municipality 4 (M4); Municipality 5 (M5); Municipality 6 (M6) and Municipality 7 (M7). The research permeated the various realities in the form of structuring the proposal of municipalization of socioeducation. This work allowed him to enter a field permeated by tensions, transposed by limits and possibilities, which increasingly require policies capable of building a network of care that enables the individual and social protection of children, adolescents and their families.